Designs and prototypes of mobile robots - Ceccarelli, Marco; Kececi, Emin Faruk (Automation and control collection., 2015)
Interdisciplinary work for engineering developments of mobile robots, in both old and new applications. This book and its companion can be used as a graduate level course books or guide books for the practicing engineer who is working on a specific problem which is described in one of the chapters.